Preparation method, product and application of C / ZnO / chitosan composite material
By preparing C/ZnO/chitosan composite materials, the problem of insufficient load rate and controlled release effect of drug carriers is solved, and the efficient load and controlled release of drugs are achieved, and good antibacterial properties are provided, which are suitable for industrial production.
Patent Information
- Application Number
- CN202510626946.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-15
- Publication Date
- 2025-08-08
AI Technical Summary
The existing drug carriers still need to improve in terms of drug loading rate and controlled release effects, especially polymer nanomaterials have shortcomings in anti-cancer drug delivery systems.
The preparation method of C/ZnO/chitosan composite is adopted to synthesize C/ZnO through solvothermal reaction, and then react with chitosan under alkaline conditions to form C/ZnO/chitosan composite material for loading and controlled release of drugs.
It achieves the efficient loading and significant controlled release effect of the drug, and shows good antibacterial properties, which is suitable for industrial large-scale production.
Smart Images

Figure CN120437085A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of drug carrier preparation, and in particular to a preparation method, product and application of a C / ZnO / chitosan composite material. Background Art
[0002] Advances in nanotechnology have greatly advanced the development of nanomedicine. Modern nanotechnology offers the possibility of targeted delivery of anticancer drugs to tumor sites, thereby minimizing toxicity and optimizing drug efficacy. Over the years, numerous drug delivery vehicles have been developed for anticancer drug delivery, such as polymer nanoparticles, solid lipids, and inorganic nanoparticles. Consequently, significant progress has been made in this field, particularly in polymer-based anticancer drug delivery systems. Polymeric micro- and nanomaterials are biodegradable and have low toxicity, and the composition and structure of polymers can be engineered to manipulate their drug delivery properties. However, the drug loading efficiency and controlled release efficacy of current drug delivery vehicles still need to be further improved. Summary of the Invention
[0003] Based on the above content, the present invention provides a preparation method, product and application of a C / ZnO / chitosan composite material.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is a method for preparing a C / ZnO / chitosan composite material, comprising the following steps:
[0006] Step 1, uniformly dispersing zinc salt and carbon source in an organic solvent to carry out a solvothermal reaction to obtain C / ZnO;
[0007] Step 2: Dispersing the C / ZnO and chitosan in solvent A, and reacting under alkaline conditions to obtain a C / ZnO / chitosan composite material.
[0008] In a preferred embodiment of the present invention, in step 1, the zinc source is zinc acetate; the carbon source is glucose; and the ratio of the zinc source to the carbon source is (2.00-2.40) mmol: (0.18-0.22) g.
[0009] In a preferred embodiment of the present invention, in step 1, the organic solvent is ethylene glycol.
[0010] In a preferred embodiment of the present invention, in step 1, the pH of the solvothermal reaction is 10.1; the temperature of the solvothermal reaction is 160° C., and the time is 24 h.
[0011] In step 1, after the solvothermal reaction is completed, the step further includes centrifugation, washing the solid obtained by centrifugation, and then drying it at 60° C. for 6 hours.
[0012] In a preferred embodiment of the present invention, in step 2, the mass ratio of the C / ZnO to the chitosan is (0.90-1.10):(0.90-1.10); the solvent A is an aqueous solution of acetic acid with a mass concentration of 1%; and the mass volume ratio of the C / ZnO to the solvent A is (0.90-1.10) g:(90-110) ml.
[0013] In the present invention, the amount of solvent A directly affects the concentration of the reaction system, and further affects the morphology and properties of the composite material; therefore, the present invention preferably limits the mass volume ratio of C / ZnO to solvent A to the above ratio.
[0014] In a preferred embodiment of the present invention, in step 2, the pH of the reaction is 10; the temperature of the reaction is 60° C.; and the reaction time is 3 h.
[0015] In some specific embodiments of the present invention, the pH of the reaction system is adjusted to alkaline by adding sodium hydroxide solution.
[0016] In step 2, after the reaction is completed, the step further includes centrifugation, washing the solid obtained by centrifugation, and then drying it at 80° C. for 12 hours.
[0017] The second technical solution of the present invention is a C / ZnO / chitosan composite material prepared according to the above preparation method.
[0018] The third technical solution of the present invention is the use of the above-mentioned C / ZnO / chitosan composite material in the preparation of sustained-release drugs.
[0019] A fourth technical solution of the present invention is a sustained-release drug, which is prepared by dissolving a C / ZnO / chitosan composite material and 5-fluorouracil in water and stirring the solution in the dark.
[0020] In a preferred embodiment of the present invention, the mass ratio of the C / ZnO / chitosan composite material to the 5-fluorouracil is (0.25-2):1; and the stirring time is 12-48 hours.
[0021] The present invention discloses the following technical effects:
[0022] The preparation method of the present invention is simple and easy to industrialize and mass-produce; the C / ZnO / chitosan composite material prepared by the method of the present invention can realize efficient loading of the drug (5-fluorouracil), has a significant controlled-release effect on the drug, and exhibits a good antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the infrared spectrum of C / ZnO prepared in Example 1.
[0024] Figure 2 This is the XRD spectrum of C / ZnO prepared in Example 1.
[0025] Figure 3 These are SEM images of C / ZnO prepared in Example 1 at different magnifications; a) 1.6k, b) 10k, c) 20k, d) 30k.
[0026] Figure 4 This is the EDS energy spectrum of C / ZnO prepared in Example 1; among them, a) Zn-K, b) OK, c) CK, d) total distribution spectrum.
[0027] Figure 5 TG-DTA curve of C / ZnO prepared in Example 1 under air atmosphere.
[0028] Figure 6 XPS spectra of C / ZnO prepared in Example 1; wherein: a) full XPS spectrum of C / ZnO, b) high-resolution Zn 2p spectrum of C / ZnO, c) high-resolution C1s spectrum of C / ZnO, d) high-resolution O1s spectrum of C / ZnO.
[0029] Figure 7 BET test results of C / ZnO prepared in Example 1; wherein, a) N2 adsorption-desorption isotherm, b) pore size distribution diagram.
[0030] Figure 8 The particle size and zeta potential results of C / ZnO prepared in Example 1 are as follows: a) particle size distribution of C / ZnO, b) zeta potential of C / ZnO, 5-FU, and C / ZnO / 5-FU (error bars represent the standard deviation of three independent measurements).
[0031] Figure 9 This is the drug release curve of C / ZnO prepared in Example 1.
[0032] Figure 10 The MIC results of C / ZnO / 5-FU (concentration decreases from left to right); a1 and a2 are Staphylococcus aureus, and b1 and b2 are Escherichia coli (Note: the 11th well in b1 and b2 is the positive control).
[0033] Figure 11 MBC results of C / ZnO / 5-FU; a, d) colony growth graph of 0 μg / mL drug treatment, b) colony growth graph of 37.5 μg / mL drug treatment, c) colony growth graph of 75 μg / mL drug treatment, e) colony growth graph of 55 μg / mL drug treatment, f) colony growth graph of 110 μg / mL drug treatment.
[0034] Figure 12 Evaluation of the hemolytic activity of C / ZnO prepared in Example 1.
[0035] Figure 13 This is the infrared spectrum of the C / ZnO / chitosan composite material (C / ZnO / CS) prepared in Example 2.
[0036] Figure 14 This is the XRD spectrum of C / ZnO / CS prepared in Example 2.
[0037] Figure 15 These are SEM images of C / ZnO / CS prepared in Example 2 at different magnifications; a) 1.6k, b) 10k, c) 20k, d) 30k.
[0038] Figure 16 This is the EDS spectrum of C / ZnO / CS prepared in Example 2.
[0039] Figure 17 TG-DTA curve of C / ZnO / CS prepared in Example 2 under nitrogen atmosphere.
[0040] Figure 18 This is the full XPS spectrum of C / ZnO / CS prepared in Example 2.
[0041] Figure 19 a) High-resolution Zn 2p spectrum, b) high-resolution C1s spectrum, c) high-resolution O1s spectrum, d) high-resolution N1s spectrum of C / ZnO / CS prepared in Example 2.
[0042] Figure 20 BET test results of C / ZnO / CS prepared in Example 2; a) N2 adsorption-desorption isotherm, b) pore size distribution diagram.
[0043] Figure 21 Figure 2 shows the particle size and zeta potential of C / ZnO / CS prepared in Example 2; a) particle size distribution of C / ZnO / CS, b) zeta potential of C / ZnO, C / ZnO / CS, 5-FU, and C / ZnO / CS / 5-FU (error bars represent the standard deviation of three independent measurements).
[0044] Figure 22 This is the sustained-release curve of the C / ZnO / CS drug prepared in Example 2.
[0045] Figure 23 The MIC results of C / ZnO / CS / 5-FU (the concentration decreases from left to right); a1 and a2 are Staphylococcus aureus, and b1 and b2 are Escherichia coli.
[0046] Figure 24 These are the MBC experimental results of C / ZnO / CS / 5-FU; a, d) colony growth graphs of 0 μg / mL drug treatment, b) colony growth graph of 31.25 μg / mL drug treatment, c) colony growth graph of 62.5 μg / mL drug treatment, e) colony growth graph of 43.75 μg / mL drug treatment, and f) colony growth graph of 87.5 μg / mL drug treatment.
[0047] Figure 25 Evaluation of the hemolytic activity of C / ZnO / CS prepared in Example 2. DETAILED DESCRIPTION
[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0049] The "room temperature" mentioned in the present invention, unless otherwise specified, refers to 20-30°C.
[0050] The testing method involved in the present invention is as follows:
[0051] 1. Fourier transform infrared spectroscopy (FT-IR): The instrument used in the present invention is a Spectrum 3, manufactured by Perkin Elmer, USA. During the test, potassium bromide (KBr) was used as the background sample, and the test sample was prepared by the KBr pellet method.
[0052] 2. Scanning electron microscope (SEM): A ZEISS GeminiSEM 300 scanning electron microscope produced by Carl Zeiss of Germany was used. In addition, in order to further analyze the elemental composition of the material, the present invention combined energy dispersive spectrometer to perform elemental qualitative and quantitative analysis on the sample surface.
[0053] 3. X-ray diffraction (XRD): The X-ray diffractometer model Bruker D8Advance from Bruker, Germany was used for the measurement. The diffraction target used was Cu·k α , the wavelength (λ) is 1.54060nm, the measurement range of 2θ is 10°-80°, and the continuous scanning rate is 10°·min -1 .
[0054] 4. Thermogravimetric Analyzer (TGA): The HITACHI STA200 thermogravimetric analyzer (HITACHI, Japan) was used for the measurements. All samples were tested in a nitrogen atmosphere, except for the C / ZnO sample, which was tested in air. During the test, a constant heating rate of 10°C / min was set. -1, the test temperature range is 30℃ to 800℃.
[0055] 5. X-ray Photoelectron Spectroscopy (XPS): The instrument model used is Thermo Scientific K-Alpha, produced by Thermo Fisher Scientific, USA, and uses Al Kα line as the X-ray source.
[0056] 6. Specific surface area and porosity determination (BET): The BET test of the material is performed using an auto IQ specific surface area and porosity analyzer. Before the test begins, the sample to be measured needs to be degassed for 12 hours to remove adsorbed gas and moisture in the sample.
[0057] 7. Particle Size and Zeta Potential Analysis (DLS): The instrument used was the Zetasizer Lab, manufactured by Malvern Instruments Ltd., UK. The Malvern DTS1070 potential cell was used for zeta measurements, and the DTS0012 potential cell was used for particle size measurements.
[0058] 8. Drug loading and encapsulation efficiency test
[0059] 5-FU is a good drug for treating cancer. The present invention uses 5-FU to study the encapsulation and loading effects of C / ZnO and C / ZnO / chitosan composite materials as carrier materials for drugs. The specific process is as follows: 10 mg of carrier material is dissolved in 15 ml of deionized water, ultrasonicated until fully dissolved, 5 mg, 10 mg, 20 mg, 30 mg, and 40 mg of 5-fluorouracil drugs are added to the above solution respectively, stirred in the dark for 24 h (300 r / min) at room temperature, and then the loaded samples (corresponding carriers are C / ZnO and C / ZnO / chitosan composite materials, and the loaded samples are marked as C / ZnO / 5-FU and C / ZnO / CS / 5-FU) are centrifuged, and the supernatant is measured with a UV tester for the absorbance of 5-fluorouracil at 266 nm. The drug concentration in the supernatant is calculated from the standard curve, and the encapsulation efficiency (D) of the drug delivery nanosystem is calculated according to the following formula. LE %) and drug loading (D LC %):
[0060]
[0061] Among them, M O Explained as the drug content in the carrier, M N is the total mass of the final drug-loaded carrier, M C Indicates the initial dosage of medicine.
[0062] 9. Drug sustained-release performance test
[0063] In vitro drug release performance experiments were conducted using 5-fluorouracil as a model drug. The sustained-release behavior of the drug-loaded system was systematically investigated by dynamic dialysis. The experimental procedure was as follows: A 14 kDa dialysis bag was pretreated by boiling in a 50% ethanol water bath for 30 minutes to remove surfactants and activate the membrane pore structure. A precisely weighed amount of the drug-loaded nanocomplex was sealed in the activated dialysis bag and then immersed in a release system containing 80 mL of phosphate buffered saline (PBS, pH 7.4), which simulates normal tissue fluid. At various time intervals, 3 mL of the solution was withdrawn from the release medium and replaced with fresh PBS. The absorbance of the samples at each time point was measured using a UV-Vis spectrophotometer at λmax = 266 nm. The cumulative release of 5-FU was calculated based on the standard curve equation (see the formula below), and the corresponding cumulative release versus time curves were plotted.
[0064]
[0065] 10. Antibacterial activity test and blood compatibility test
[0066] The bacterial species selected in this experiment are typical representatives of Gram-positive and Gram-negative bacteria - Staphylococcus aureus and Escherichia coli. The antibacterial activity of drugs and carriers was evaluated by the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). MIC refers to the lowest drug concentration that inhibits bacterial growth in a specific culture medium, while MBC is the lowest concentration required to kill 99.9% of bacteria. The two were used to evaluate the antibacterial and bactericidal abilities of antibacterial materials through in vitro drug sensitivity tests. The multiple dilution method was used to determine the MIC by observing the antibacterial conditions of the corresponding wells of the 96-well plate with the naked eye and resazurin staining, and the MBC value was verified by the subsequent agar coating method. The experimental process is as follows: (1) The antibacterial efficacy was evaluated by the two-fold dilution method: the sample to be tested was accurately weighed and dissolved in ultrapure water to prepare a gradient dilution stock solution. 180 μl of the concentration was standardized to 10 was injected into each well of the 96-well plate. 6CFU / ml of Staphylococcus aureus suspension was added, and then 20μl of sample solution of different concentrations was added and mixed by pipetting. A negative control group (TSB culture medium) and a positive control group (pure bacterial solution) were set up, and three parallels were set up for each concentration group. The treated microplate was placed in a 37℃ constant temperature incubator for 24 hours, and the antibacterial endpoint was determined by turbidity method - the lowest concentration that completely inhibited bacterial growth was the MIC. For the MIC test of Escherichia coli, except for using LB culture medium as the negative control, the rest of the operation procedures remained the same. (2) Select the critical concentration based on the MIC result: Take 100μl of bacterial suspension from the completely transparent well (no bacterial growth) and the first turbid well (bacterial survival), and evenly spread it on the solid agar plate. Simultaneously set up a blank control without drug treatment. After 24 hours of incubation, the colony forming units (CFU) were counted on the plate, and the group with the lowest drug concentration and no colony growth was determined as the MBC value. To ensure data reliability, all experiments were performed three times with independent repeated measurements.
[0067] The hemocompatibility of the nanomaterials was determined using a direct contact method, referring to ISO standard 10993-4 (1992). Hemolysis tests were conducted using anticoagulated whole blood from large-eared white rabbits. If the average hemolysis rate of the sample was less than or equal to 5%, the material was considered non-hemolytic. Experimental procedures: The collected whole blood was centrifuged at 2500 rpm for 10 minutes to remove the upper platelet-rich plasma and middle layer of white blood cells. The sample was then washed with phosphate-buffered saline (PBS) and centrifuged at 1500 rpm for 5 minutes. This was repeated 2-3 times until the supernatant was colorless to remove residual plasma. The washed red blood cells were diluted with PBS to a 2% red blood cell suspension. 2.5 ml of the 2% red blood cell suspension and 2.5 ml of PBS were added to the sample and incubated at 37°C for 1 hour. 2.5 ml of the 2% red blood cell suspension was added to 2.5 ml of deionized water and PBS buffer, respectively, as positive and negative controls. After the incubation, the mixture was centrifuged at 2000 rpm for 5 min. The absorbance of the supernatant at a wavelength of 540 nm was measured using a multifunctional microplate reader. The hemolysis rate (HR%) was calculated according to the following formula:
[0068]
[0069] OD (+) and OD (-) Represents the absorbance values of positive and negative controls, OD S Indicates the absorbance value of the test sample.
[0070] Unless otherwise specified, the technical solutions described in the present invention are all conventional solutions in the field, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0071] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0072] Example 1
[0073] 22 mL of a 0.1 M zinc acetate (Zn(Ac)2·2H2O) stock solution in ethylene glycol was added to 10 mL of a 0.6 M NaOH stock solution in ethylene glycol, forming a milky white mixture with a pH of 10.1. After stirring for 10 minutes, 0.2 g of glucose was added, and the resulting mixture was transferred to a 75 mL Teflon-lined stainless steel autoclave and heated at 160°C for 24 hours. Finally, the mixture was centrifuged, washed with deionized water, and dried in an oven at 60°C for 6 hours to obtain C / ZnO.
[0074] The C / ZnO prepared in Example 1 was characterized and analyzed, and its performance was studied as follows:
[0075] 1. Characterization and analysis of C / ZnO (the C / ZnO / 5-FU involved in this experiment was prepared according to the above method with m(C / ZnO):m(5-FU)=1:3)
[0076] (1)FT-IR analysis
[0077] The infrared spectrum of C / ZnO is as follows Figure 1 As shown. At 3384cm -1 There is a strong absorption in the range, corresponding to the stretching vibration of the hydroxyl group; at 471cm -1 The characteristic absorption peak of Zn-O bond can be observed, indicating the successful synthesis of ZnO. -1 The absorption peak at 1047 cm is the characteristic peak of saturated CH bond, and the stretching vibration of CC is located at 1047 cm -1 . The production of carbon in the experiment was mainly through the hydrothermal reaction of glucose, which was hydrolyzed under high temperature and high pressure to form a carbon structure. Through the characterization of infrared spectroscopy, it was found that there was a stretching vibration peak of the CC bond in the prepared material, confirming that the sample prepared after the solvent thermal reaction was a C / ZnO material. Compared with the infrared spectrum of C / ZnO, it was found that only a few characteristic peaks of the drug were observed in the spectrum of the composite C / ZnO / 5-FU. The results showed that 5-FU was successfully loaded on the carrier C / ZnO.
[0078] (2) XRD analysis
[0079] The chemical composition of the obtained C / ZnO was characterized by XRD. Figure 2 As shown by Figure 2It can be seen that the material has significant diffraction peaks at 31.8°, 34.5°, 36.3°, 56.6°, 57.0° and 68.1°. After analysis with JADE software and comparison with the standard PDF comparison card #36-1451, it was found that the interplanar spacing corresponds to the standard card one by one, and all diffraction peaks can be indexed to the (100), (002), (101), (102), (110), (103), and (112) lattice planes of hexagonal ZnO in sequence. After the addition of C, the XRD spectrum of C / ZnO still has all the characteristic peaks of ZnO, and no new peaks appear, indicating that C as a surface modifier does not affect the structure of ZnO. Furthermore, the diffraction peaks between 10° and 30° become noticeably rougher, primarily attributable to amorphous carbon, indicating successful incorporation of the carbon material into the ZnO nanospheres. The absence of any other impurities in the spectrum indicates the absence of impurities other than ZnO and carbon in the sample, demonstrating the high purity of the C / ZnO prepared by the solvothermal method. The C / ZnO diffraction peaks are intense and sharp, indicating good crystallinity.
[0080] (3) SEM analysis
[0081] The morphology of C / ZnO was studied by SEM analysis. Figure 3 As shown (in the figure, a) 1.6k, b) 10k, c) 20k, d) 30k); by Figure 3 It can be seen that C / ZnO is in the form of spherical particles, which are evenly distributed and have a size distribution between 1-2 μm. It is observed that the surface morphology of C / ZnO is rough and is composed of a large number of small particles. The polymerization of C / ZnO material is mainly due to the addition of glucose during the synthesis of ZnO. Under solvent thermal conditions, glucose will undergo various chemical reactions, which leads to the production of a complex mixture of some aromatic compounds and oligosaccharides. These organic compounds can increase the viscosity of the resulting solution, leading to aggregation into spheres. In addition, the growth direction of ZnO is also affected by glucose. The high negative charge of glucose will mainly interact with the positively charged (0001) surface of the ZnO crystal. These interactions reduce the surface free energy of the positive plane and inhibit any directional growth of the ZnO nucleus, resulting in an equiaxed or spherical particle morphology. The EDS surface scanning element distribution of C / ZnO is shown in Figure 2. Figure 4 As shown, observe Figure 4 The Zn, O, and C elements in the C / ZnO are uniformly distributed, with Zn, O, and C accounting for 30.87%, 33.87%, and 35.26%, respectively. The elemental ratios clearly indicate that some carbon has been successfully incorporated into the ZnO crystal structure. EDS spectra confirm that the material is a C / ZnO nanomaterial.
[0082] (4) TGA analysis
[0083] The thermal stability of C / ZnO was characterized by a simultaneous thermal analyzer, such as Figure 5 As shown. During the gradual heating process, the weight loss of the C / ZnO material reached 15.1%, and as the temperature continued to rise, the weight tended to stabilize. When the temperature was raised from room temperature 25°C to 235°C, a small amount of free water adsorbed on the surface of C / ZnO evaporated, resulting in a weight loss of approximately 4.5%. Subsequently, during the heating process from 235°C to 800°C, the C material in C / ZnO underwent thermal decomposition, resulting in a weight loss of 10.6%. The analysis results showed that C was successfully incorporated into ZnO, and the C loading amount was 10.6%, which was consistent with the EDS results. The incorporation of an appropriate amount of C not only affects the crystallization process of ZnO, thereby controlling the shape and size of ZnO particles, but also a moderate C loading amount easily leads to the material having a higher specific surface area and a larger pore structure, which enables them to better adsorb or load other substances and improve the sustained release performance.
[0084] (5) XPS analysis
[0085] XPS technology is used to detect the chemical element composition and element valence structure in the sample. In order to further characterize the sample, the XPS full scan spectrum of C / ZnO and the high resolution spectrum of each element were measured. The XPS full scan spectrum of C / ZnO is as follows Figure 6 As shown, the elemental composition of the sample is Zn, O, and C, which corresponds to the mapping results determined previously, and the atomic number percentages of the three elements Zn, O, and C in the composite material are 26.16%, 37.01%, and 36.83%, respectively. Figure 6 b)-d) show the high-resolution spectra of Zn 2p, C 1s, and O1s of C / ZnO materials. Figure 6 Figure b) shows that the Zn 2p spectrum consists of two symmetrical peaks. The position of the Zn 2p peak and its spin-orbit splitting energy are basically consistent with the standard values of ZnO, which confirms that Zn in the sample exists in a divalent oxidation state. Figure 6 Figure c) shows the C1s XPS spectrum of the prepared spherical C / ZnO nanostructure. Two peaks centered at 284.8 and 286.4 eV can be identified, corresponding to CC and CO, respectively. The peak at 286.4 eV is attributed to residual carbon, indicating the presence of residual carbon in C / ZnO. It can be seen that the binding energy of C shifts toward high energy, which may be mainly due to the substitution of C for Zn doping during sample preparation. Zinc atoms in ZnO are usually Zn. 2+, and carbon has a strong electronegativity, which will cause the electron density of the surrounding atoms to change. The substitution of carbon in ZnO may cause changes in the electronic interaction between carbon atoms and oxygen atoms, thereby affecting the electron cloud density of carbon, making the C1s electrons more strongly attracted, resulting in an increase in binding energy. In addition, the carbon atom replaces zinc and forms a new bond (CO) with oxygen. This local chemical environment change may also lead to an increase in the binding energy of the C1s peak. The high-resolution spectrum of O 1s is shown in Figure 2. Figure 6 As shown in (d), it is found through fitting that for C / ZnO, the centers of the fitting curves are located at 532.28eV, 531.39eV and 530.37eV respectively; the peak at 530.37eV can be attributed to the ZnO lattice being occupied by Zn 2+ ions and surrounding O 2- ions. The peak at 531.39 eV should be attributed to surface oxygen species. The higher binding energy peak at 532.28 eV may have different causes, such as oxygen vacancies, hydroxyl groups, or CO bonds.
[0086] (6) BET analysis
[0087] In order to further understand the porous structure and pore size distribution of the prepared C / ZnO, the BET method was used to measure the specific surface area of N2 adsorption-desorption, and the Barrett-Joyner-Halenda (BJH) method was used to measure the pore size distribution of the adsorption and desorption branches of the N2 isotherm. As shown in 7a), the N2 adsorption-desorption isotherm of spherical C / ZnO presents a type IV, indicating that there are rich mesoporous structures in the structure. The material composed of plate-like particle aggregates (loose aggregates) has a wide hysteresis loop in the relative pressure range of 0.3 to 1.0, forming slit-like pores. In addition, it can be seen from 7b) that the pore size distribution is relatively narrow, with a sharp peak near 4.7nm. The total specific surface area of C / ZnO is approximately 14457.679m 2 / g, the pore volume and average pore diameter are 16.243cc / g and 4.76nm respectively. The high specific surface area and narrow mesoporous channels are conducive to improving the adsorption capacity.
[0088] (7) DLS analysis
[0089] The particle size distribution of the nanocomposites was studied using dynamic light scattering. Figure 8As shown, the average size of the C / ZnO material is 1560 nm, consistent with scanning electron microscopy results. The polydispersity index of C / ZnO is 0.0673, indicating that the C / ZnO nanomaterial exhibits excellent water dispersibility. Zeta potential, a core parameter in nanotechnology, quantifies the relationship between surface charge and stability, providing key theoretical support for drug delivery. The zeta potential of the C / ZnO nanomaterial is -14.15 mV. The negative surface charge of the material is primarily due to the ionization of oxygen-containing functional groups on the carbon component and the deprotonation of hydroxyl groups on the ZnO surface, indicating good stability. Generally, the surface zeta potential indicates the external repulsive force between the outer surfaces of nanoparticles. As the value increases, the repulsive force increases, which can prevent adhesion and enhance electrostatic stability. Furthermore, negatively charged nanocomposites are metabolized more slowly in the blood than positively charged nanocomposites, resulting in their longer circulatory retention. Due to the high affinity between negatively charged nanoparticles and the positively charged plasma membrane, negatively charged nanocomposites are more biocompatible than positively charged nanocomposites. The potential of the composite system was -16.84 mV, reflecting the charge superposition effect between the drug and the carrier. The absolute value of the zeta potential was positively correlated with the surface charge density of the particles. Larger surface areas and higher surface charge densities were associated with higher absolute zeta potential values. The high absolute value of the drug-loaded material's potential was primarily due to the loading of 5-fluorouracil molecules.
[0090] 2. Performance study of C / ZnO
[0091] (1) Study on drug loading and release behavior of C / ZnO
[0092] To investigate the effect of the C / ZnO / drug (5-FU) mass ratio on the encapsulation efficiency and drug loading, 15 mL of deionized water, 10 mg of carrier, and m(C / ZnO):m(5-FU) ratios of 2:1, 1:1, 1:2, 1:3, and 1:4 were used. The mixture was stirred at room temperature in the dark, and the supernatant was centrifuged to prepare C / ZnO / 5-FU. The encapsulation efficiency and drug loading were calculated.
[0093] (i) 5-Fluorouracil drug loading
[0094] The encapsulation efficiency results are shown in Table 1, and the drug loading results are shown in Table 2.
[0095] Table 1 Encapsulation efficiency results
[0096]
[0097] Table 2 Drug loading results
[0098]
[0099] The data in Table 1 show that the drug encapsulation efficiency decreases with increasing drug content. The optimal condition for C / ZnO loading of 5-FU is a carrier-to-drug mass ratio of 2:1, at which the drug encapsulation efficiency is 62.8%. The data in Table 2 show that drug loading increases with increasing drug content. At a carrier-to-drug mass ratio of 1:4, drug loading begins to decline, indicating that drug loading has reached saturation. In summary, the optimal condition for C / ZnO loading of 5-FU is a carrier-to-drug mass ratio of 1:3, at which the drug loading reaches its maximum of 32.8%. Subsequent experiments were conducted using C / ZnO / 5-FU prepared with a m(C / ZnO):m(5-FU) ratio of 1:3.
[0100] (ii) Drug release test of C / ZnO
[0101] To study the release behavior of 5-FU under in vitro triggering, a neutral (pH 7.4) release system was selected to simulate body fluid. Figure 9 Figure 3 shows the cumulative release behavior of 5-FU from C / ZnO / 5-FU in phosphate buffer solution at pH 7.4. At room temperature, the drug release reached 33.0% within 8 hours, consistent with the "burst release effect". The main reason may be the mesopores (average pore size 4.76nm) and high specific surface area (BET 14457.679m 2 The ZnO surface is characterized by a high surface area (1000 nm) and a high molecular weight (1000 nm). The surface area (1000 nm) of the ZnO substrate (1000 nm) allows the active substance (drug) loaded on the surface to preferentially contact the medium, leading to rapid dissociation via physical adsorption and weak chemical bonds. Within 10-25 hours, the drug release rate significantly decreases, reaching a cumulative release rate of 40.0%. This is likely due to the formation of hydrogen or coordination bonds between the hydroxyl groups on the ZnO surface and the amino / NH groups of the active substance (such as 5-fluorouracil), requiring higher activation energy for dissociation. These results demonstrate the significant potential of C / ZnO for drug delivery.
[0102] (2) Study on the antibacterial activity and blood compatibility of C / ZnO
[0103] (i) Study on the antibacterial activity of C / ZnO
[0104] ① Determination of minimum inhibitory concentration (MIC), the results are as follows Figure 10 and as shown in Table 3.
[0105] Table 3 Minimum inhibitory concentration results of the release solution in each group
[0106]
[0107] Figure 10Figures a1 and a2 show the MIC results of C / ZnO / 5-FU against Staphylococcus aureus at different sample concentrations. The results demonstrate that C / ZnO / 5-FU exhibits moderate antibacterial activity against S. aureus, and that the turbidity of the solution decreases with increasing C / ZnO / 5-FU dosage. From left to right, the concentrations of C / ZnO / 5-FU are 300 μg / ml, 150 μg / ml, and so on. After resazurin staining, the color of the wells in the fifth column changes from blue to red (the wells in the fourth column are completely clear), indicating that 37.5 μg / ml is the minimum inhibitory concentration of C / ZnO / 5-FU against S. aureus. Figure 10 Figures b1 and b2 show the MIC results of C / ZnO / 5-FU against E. coli at different sample concentrations. From left to right, the C / ZnO / 5-FU concentrations are 220 μg / ml, 110 μg / ml, and so on. Visual observation of the color changes in the well plate revealed that 55.0 μg / ml was determined to be the minimum inhibitory concentration (MIC) of C / ZnO / 5-FU against E. coli.
[0108] ② Determination of minimum bactericidal concentration (MBC), the results are as follows Figure 11 shown.
[0109] The MBC observation results of C / ZnO / 5-FU against Staphylococcus aureus and Escherichia coli are as follows Figure 11 The changes in the number of Staphylococcus aureus colonies during the culture process are shown in Figure 11 (a)-c) Control group Figure 11 The initial cell count of Staphylococcus aureus in (a) is approximately 110 CFU / g. As the drug concentration increases (from left to right), the number of S. aureus colonies decreases significantly. In the 2MIC group, the total bacterial count is 0 CFU / g, so the MBC of C / ZnO / 5-FU against S. aureus is 75.0 μg / ml. The changes in the number of E. coli colonies during the culture are shown in Figure 2. Figure 11 In (d)-f), the changes in E. coli colony counts were similar to those of S. aureus. In the 2MIC group, the total bacterial count was 0 CFU / g, so the MBC of C / ZnO / 5-FU against E. coli was 110 μg / ml.
[0110] The results of the antibacterial experiment showed that the drug-loaded C / ZnO exhibited significant inhibitory effects on both test strains. Specifically, its MIC and MBC for Staphylococcus aureus and Escherichia coli were 37.5μg / mL and 75.0μg / mL (Staphylococcus aureus), 50.0μg / mL and 100μg / mL (Escherichia coli), respectively. It is worth noting that compared with the antibacterial efficacy of pure 5-FU (MIC = 46.9μg / mL, MBC = 93.8μg / mL for Staphylococcus aureus; MIC = 55.0μg / mL, MBC = 110μg / mL for Escherichia coli), the drug-loaded C / ZnO system showed better antibacterial activity, with its MIC and MBC values reduced by approximately 20.0% and 20.0% (Staphylococcus aureus) and 9.10% and 9.10% (Escherichia coli), respectively. The enhanced antibacterial performance of drug-loaded C / ZnO may be due to the ROS oxidation of ZnO, the 2+ Dissolution and physical destruction mechanisms. The introduction of a carbon matrix may achieve synergistic effects by enhancing photocatalytic efficiency, regulating ion release, and optimizing adsorption properties. Furthermore, the C / ZnO system is more effective against Staphylococcus aureus than Escherichia coli, primarily because the Gram-positive bacterial cell wall carries a more negative charge, which leads to more pronounced electrostatic adsorption of ZnO, resulting in a stronger antibacterial effect.
[0111] (ii) Blood compatibility study of C / ZnO
[0112] In the hemolysis test, Figure 12 (Positive in the figure indicates positive control, and Negative indicates negative control.) The blood sample incubated with deionized water appears as a red, transparent solution, indicating that red blood cells have ruptured and dissolved, resulting in hemolysis. However, C / ZnO does not produce visible hemolysis, indicating that the material can meet the requirements of general biological experiments. Figure 12 The results showed that the relative hemolysis rate of each group was less than 5%, which indicated that the C / ZnO material had good blood compatibility.
[0113] Example 2
[0114] 1 g of C / ZnO prepared in Example 1 was dissolved in 100 ml of 1% aqueous acetic acid. 1 g of chitosan was added to this solution, and the mixture was repeatedly stirred and sonicated for 30 minutes to obtain a homogeneous solution. 1 M NaOH was added dropwise to this solution until the pH reached 10, turning the solution milky white. Finally, the solution was heated in a 60°C water bath for 3 hours, then filtered and washed multiple times with distilled water. The precipitate was dried in a 50°C oven for 1 hour to obtain a C / ZnO / chitosan composite material, designated C / ZnO / CS.
[0115] The C / ZnO / CS prepared in Example 2 was characterized and analyzed, and its performance was studied as follows:
[0116] 1. Characterization and Analysis of C / ZnO / CS (C / ZnO / CS / 5-FU involved in this experiment was prepared according to the above method with m(C / ZnO / CS):m(5-FU)=1:4)
[0117] (1)FT-IR analysis
[0118] The infrared spectrum of C / ZnO / CS is shown in Figure 13 In the infrared spectrum of C / ZnO / CS, different absorption peaks correspond to different chemical bonds and functional groups. By analyzing these peaks, we can gain a deeper understanding of the composition and properties of the sample. -1 The broad peak near 1595 cm is the stretching vibration peak caused by the intermolecular hydrogen bond between -OH and -NH2. -1 Nearby is the amide II band (NH bending vibration), 1655 cm -1 Nearby is the amide I band (C=O stretching vibration), 1157 cm -1 The COC antisymmetric stretching vibration on the CS polysaccharide structure is nearby, and the above is a typical characteristic peak of CS. -1 The bending vibration of Zn-O is nearby, which is the characteristic absorption peak of ZnO, indicating that C / ZnO and CS are successfully composited. It is not difficult to find in the infrared spectrum of C / ZnO / CS / 5-FU (5-fluorouracil) that the peaks at 1260-1700 cm -1 The characteristic bands of the drug are shown near the 5-FU peak, which indicates that the drug and the carrier are successfully complexed. -1 The blue shift of the regional absorption peak may be due to the hydrogen bonding between the nitrogen atoms (such as nitrogen in the nitrogen heterocycle) and fluorine atoms in the 5-FU molecule and the hydrogen atoms (from chitosan CS or possible hydroxyl groups) in the C / ZnO / CS composite material, which leads to the shift of the absorption peak.
[0119] (2) XRD analysis
[0120] The XRD patterns of the prepared C / ZnO / CS materials are shown in Figure 2. Figure 14As shown. The X-ray diffraction pattern of C / ZnO shows characteristic peaks observed at 31°, 34°, 36°, 47°, 56°, 62° and 67°, which correspond to the diffraction peak positions and intensities of (100), (002), (101), (102), (110), (103) and (112) of ZnO, which are consistent with the diffraction peaks of the standard and its crystal structure. Compared with the X-ray diffraction pattern of C / ZnO, the XRD spectrum of C / ZnO / CS has a diffraction peak at about 20°, which corresponds to the (200) plane of CS. The disappearance of the CS peak near 10° may be due to the destruction of intermolecular hydrogen bonds caused by the coordination of zinc ions with hydroxyl and amino groups (there are strong intermolecular hydrogen bonds between the amino and hydroxyl groups of CS). The presence of the 20° diffraction peak indicates that C / ZnO and CS are successfully composited.
[0121] (3) SEM analysis
[0122] Figure 15 Scanning electron microscope images at different magnifications are shown to observe the microstructure of the C / ZnO / CS composite. At low magnification, the particles appear loosely aggregated, forming multiple clusters. This indicates that there is a certain interaction between carbon-doped zinc oxide and chitosan, resulting in a certain degree of agglomeration, with smaller secondary particles or aggregates attached to the surface of larger particles. At high magnification, the surface features of the small particles are more obvious, and CS exhibits a distinct granular structure with abundant pores on its surface. The addition of CS increases the specific surface area of the material and improves its adsorption properties.
[0123] like Figure 16 As shown, elemental mapping confirmed the presence of Zn, O, C, and N. The results show that Zn accounts for 14.2%, O accounts for 26.29%, C accounts for 53.45%, and N accounts for 6.07%. Since CS is the sole source of N, the relatively small proportion of N atoms indicates that C / ZnO and CS form a composite. Combined with SEM images, Zn is primarily distributed in the larger spherical portion, while N is primarily distributed around the spheres. The distribution of Zn, O, C, and N confirms that this material is a C / ZnO / CS composite and is free of other impurities.
[0124] (4) TGA analysis
[0125] Figure 17The TG-DTA curves of the C / ZnO / CS material under a nitrogen atmosphere are shown. The TGA curves of the sample are divided into three main weight loss stages. In the first stage, when the temperature is increased from room temperature to 200°C, the sample mass decreases by 6% due to the evaporation of adsorbed and bound water in the material. The mass loss in the 200-600°C stage is attributed to the decomposition of CS, which exhibits two degradation stages. The TGA curve shows significant mass loss in the 200-350°C stage, corresponding to the thermal decomposition of chitosan. The DTA curves exhibit an exothermic peak in this range, indicating that the decomposition of chitosan is an exothermic reaction, generating small molecules (such as CO2 and H2O). As the temperature is further increased, the TGA curves show a continued mass loss. In the 350-600°C stage, chitosan further carbonizes, forming a carbon skeleton, while the residual organic components continue to decompose and lose mass. There is a small amount of mass loss in the 600-800 °C stage, and the corresponding DTA curve shows an exothermic peak in this range. This is due to the presence of reducing substances (such as carbon) in the composite material. ZnO may begin to be reduced above 600 °C, resulting in weight loss.
[0126] (5) XPS analysis
[0127] Figure 18 The full XPS spectrum of C / ZnO / CS is shown. From the elemental composition, the surface of the C / ZnO / chitosan composite material is mainly composed of C, O, Zn and a small amount of N, which is consistent with the EDX results, indicating that chitosan and ZnO are successfully composited.
[0128] The spectra of individual components were deconvoluted to assign their binding properties. Figure 19 The high-resolution spectra of each element are shown. Figure 19 As can be seen in a), the Zn 2p XPS spectrum of C / ZnO / CS can be divided into two Gaussian peaks: Zn 2p 3 / 2 and Zn 2p 1 / 2 The binding energies of these two peaks are 1044.66eV and 1021.58eV, respectively, and their spin-orbit splitting energy is 23.08eV, indicating that the Zn in these two samples is in the Zn 2+The C1s spectrum of C / ZnO / CS reveals a variety of carbon chemical states. The first peak at 284.8 eV is attributed to C-C (sp3) bonds; the second peak at 286.29 eV is associated with CO, such as hydroxyl (-OH) or ether (CO-C) bonds; and the third peak at 288.20 eV is attributed to C=O and OCO bonds, corresponding to carbonyl (C=O) or ester (OC=O) structures in chitosan. Compared to the high-resolution C1s spectrum of C / ZnO, the C / ZnO / CS spectrum shows a slight shift in the characteristic peaks of CO, C=O, and OCO, and a change in their corresponding intensities, indicating an interaction between chitosan functional groups and C / ZnO. In the high-resolution O1s XPS spectrum of C / ZnO / CS, the binding energies corresponding to the two Gaussian function curves fitted are 530.54 eV and 532.19 eV, respectively. The peak at 530.54 eV is associated with the O atoms in the Zn-O bond, and the peak at 532.19 eV is due to chemically adsorbed oxygen. The deconvolution of the N1s spectrum of C / ZnO / CS reveals the contributions of three peaks at 399.40 eV, 398.56 eV, and 400.42 eV, which are mainly attributed to -NH-, -NH2, and -NH 3+ .
[0129] (6) BET analysis
[0130] Figure 20 The adsorption-desorption isotherm and pore size distribution of C / ZnO / CS are shown in Figure 2. Figure 20 As shown in a), the amount of adsorbed gas in C / ZnO / CS nanomaterials increases with the increase of the partial pressure of the components. When the pressure approaches P0 (close to the saturated vapor pressure), the pores of the mesopores begin to be filled with gas, resulting in a rapid increase in the adsorption amount. The nitrogen adsorption-desorption curve of this sample is a type IV isotherm, and the adsorption / desorption hysteresis loop is relatively obvious, indicating that the mesopores in the C / ZnO / CS material are dominant. The test results show that the BET specific surface area of the C / ZnO / CS material is 111.42 m 2 / g. As shown in Figure 20b), the pore size distribution of this sample is mainly between 2nm and 30nm, with a concentration of around 3.837nm. The pore volume and average pore diameter are 0.635cc / g and 23.24nm, respectively. A larger specific surface area means that the drug carrier has more surface area per unit mass, which can provide more reaction or adsorption sites. The addition of CS reduces the pore volume of the material. Smaller pores lead to a slower release rate of the drug from the carrier material, which can enhance the sustained release effect of the drug.
[0131] (7) DLS analysis
[0132] The particle size distribution of the nanocomposites was studied using dynamic light scattering. Figure 21As shown in Figure 3, the prepared C / ZnO / CS material exhibits a narrow size distribution with monodisperse characteristics. The successful preparation of the C / ZnO / CS composite was further confirmed by zeta potential. Figure 21 b) shows the Zeta potential of C / ZnO, C / ZnO / CS, 5-FU, and C / ZnO / CS / 5-FU. As shown in the figure, the Zeta potential of C / ZnO material is -14.15mV. This is because the surface of carbon materials often contains abundant oxygen-containing functional groups (such as hydroxyl -OH). These groups are easily ionized in neutral solutions, releasing H + After surface modification with chitosan, Zeta increased to 5.03 mV, which is due to the amino group (-NH3 + ) is protonated, neutralizing the negative charge on the C / ZnO surface, thereby increasing the Zeta potential. The positive potential of C / ZnO / CS can enhance the interaction with the negatively charged tumor cell membrane (Zeta≈-20mV) through electrostatic attraction, promoting targeted accumulation. After 5-FU loading, the potential reversed to -3.96mV, indicating that the NH of 5-FU (3200cm -1 ) forms hydrogen bonds with the hydroxyl groups (-OH) of CS. Furthermore, the potential of C / ZnO / CS / 5-FU is between that of C / ZnO / CS and 5-FU, indicating that the charge distribution is regulated by the drug-carrier synergistic effect rather than a single mechanism.
[0133] 2. Drug loading and release behavior of C / ZnO / CS
[0134] (1) 5-Fluorouracil drug loading
[0135] The experiment primarily investigated the effects of the carrier-to-drug mass ratio and loading time on carrier drug loading. Deionized water was used in 15 mL, the carrier mass was 10 mg, and the mass ratios m(C / ZnO / CS):m(5-FU) were 2:1, 1:1, 1:2, 1:3, and 1:4. The mixture was stirred at room temperature in the dark for 12, 24, and 48 hours (at 300 rpm). The supernatant was centrifuged and the encapsulation efficiency and drug loading were calculated.
[0136] Table 4 Effects of carrier to drug mass ratio and stirring time on encapsulation efficiency
[0137]
[0138] Table 5 Effects of carrier to drug mass ratio and stirring time on drug loading
[0139]
[0140] The data in Tables 4 and 5 indicate that drug loading is positively correlated with the carrier-to-drug mass ratio. A carrier-to-drug mass ratio of 1:4 significantly improves drug loading and encapsulation efficiency. In summary, the optimal conditions for 5-FU loading on C / ZnO / CS are a carrier-to-drug mass ratio of 1:4 and a loading time of 48 hours. The study found that the drug loading of the C / ZnO / CS composite material was significantly improved compared to that of C / ZnO. This is likely due to the fact that the introduction of chitosan provides more hydroxyl groups as crosslinking points, creating more sites for drug loading and increasing drug loading. Subsequent experiments were conducted using a C / ZnO / CS / 5-FU composite prepared with a m(C / ZnO / CS):m(5-FU) ratio of 1:4 and a stirring time of 48 hours.
[0141] (2) Drug release test of C / ZnO / CS
[0142] In order to verify that C / ZnO can further play a sustained-release role after being compounded with chitosan, the present invention continuously tested the in vitro drug release experiment for 50 hours. The results showed that compared with C / ZnO, C / ZnO / CS had a longer drug sustained-release time. The drug release of C / ZnO / CS was about 63.1% at 39 hours, showing a slowly rising trend, while the release of C / ZnO tended to stagnate at the 24th hour (the cumulative release rate reached 40.0% at 24 hours), indicating that the adsorption-desorption equilibrium was reached between the drug and the material. This shows that the composite of C / ZnO material and chitosan significantly improved the sustained-release performance of 5-FU. The reason is that the amino group (-NH2) and hydroxyl group (-OH) on the chitosan molecular chain can react with the Zn on the surface of C / ZnO. 2+ Or hydroxyl (-OH) groups are bound together through coordination bonds, hydrogen bonds or covalent bonds to form a stable three-dimensional cross-linked network. This structure delays the diffusion path of the active substance and reduces the release rate.
[0143] (3) Study on the antibacterial activity of C / ZnO / chitosan composite materials
[0144] (i) Determination of minimum inhibitory concentration (MIC)
[0145] Figure 23 Figures a1 and a2 show the MIC results of C / ZnO / CS / 5-FU against Staphylococcus aureus at different sample concentrations. The results demonstrate that C / ZnO / CS / 5-FU exhibits moderate antibacterial activity against S. aureus, and that the turbidity of the solution decreases with increasing addition. From left to right, the concentrations of C / ZnO / CS / 5-FU are 250 μg / ml, 125 μg / ml, and so on. After resazurin staining, the color of the fifth column of wells changes from blue to red (the fourth column of wells remains completely clear), thus establishing 31.3 μg / ml as the minimum inhibitory concentration of C / ZnO / CS / 5-FU against S. aureus. Figure 23Figures b1 and b2 show the MIC results of C / ZnO / CS / 5-FU against E. coli at different sample concentrations. From left to right, the concentrations of C / ZnO / CS / 5-FU are 350 μg / ml, 175 μg / ml, and so on. Visual observation of the color changes in the well plate revealed that the minimum inhibitory concentration (MIC) of C / ZnO / CS / 5-FU against E. coli was 43.8 μg / ml. Comparison with the antibacterial data for C / ZnO revealed that the chitosan-coated C / ZnO material exhibited lower MICs than the C / ZnO material without chitosan, with the chitosan-coated C / ZnO material exhibiting the lowest value. The MBC trend was consistent with the MIC. The combination of CS and C / ZnO proved highly effective, inhibiting bacterial growth at concentrations significantly lower than that of C / ZnO alone. This phenomenon may be attributed to the CS conformation on the C / ZnO surface, which enhances the positive particle surface charge. This may promote more efficient interactions between C / ZnO materials and microorganisms, leading to increased Zn accumulation within bacterial cells and excessive production of reactive oxygen species.
[0146] Table 6 Minimum inhibitory concentration results of the release solution in each group
[0147]
[0148] (ii) Determination of minimum bactericidal concentration (MBC)
[0149] The MBC observation results of C / ZnO / CS / 5-FU against Staphylococcus aureus and Escherichia coli are as follows Figure 24 The changes in the number of Staphylococcus aureus colonies during the culture process are shown in Figure 23 In a)-c), the cell counts of Staphylococcus aureus from left to right are 70 CFU / g, 9 CFU / g, and 0 CFU / g, respectively. Therefore, the MBC of C / ZnO / CS / 5-FU against Staphylococcus aureus is 62.5 μg / ml. The changes in the number of Escherichia coli colonies during the culture process are shown in Figure 1. Figure 23 In panels d)-f), the E. coli cell counts from left to right are 34 CFU / g, 10 CFU / g, and 0 CFU / g, respectively. Therefore, the MBC of C / ZnO / CS / 5-FU against E. coli is 87.5 μg / ml.
[0150] Antibacterial substances play a vital role in sustained drug release. Here, the inhibitory effects of C / ZnO / 5-FU and C / ZnO / CS / 5-FU on Escherichia coli and Staphylococcus aureus were examined by measuring their MICs. The present invention found that the MICs of C / ZnO / 5-FU and C / ZnO / CS / 5-FU against Escherichia coli were 55.0μg / mL and 43.8μg / mL, respectively. The detection concentrations for Staphylococcus aureus were 37.5μg / mL and 31.3μg / mL, respectively. Compared with C / ZnO / 5-FU, C / ZnO / CS / 5-FU showed higher antibacterial efficacy. This study emphasizes the efficacy of the combined use of C / ZnO and CS in combating Escherichia coli and Staphylococcus aureus, and provides innovative ideas for the development of antibacterial materials and the expansion of their applications in multiple fields.
[0151] (4) Study on the blood compatibility of C / ZnO / chitosan composite materials
[0152] Compared with the initial material C / ZnO, the surface of the composite sample C / ZnO / CS has a lower hemolysis rate. The possible reason is that the pure C / ZnO material is prone to agglomeration due to its high surface energy, releasing excessive Zn 2+ This may disrupt the integrity of red blood cell membranes. However, chitosan, through physical coating or chemical cross-linking, effectively disperses ZnO nanoparticles, slowing ion release and reducing direct blood toxicity. Furthermore, the introduction of chitosan creates a more hydrophilic surface environment, reducing nonspecific adsorption of blood components and thereby inhibiting platelet aggregation and thrombosis. Hemolysis rate values indicate that polymer coating significantly improves the blood compatibility of C / ZnO materials.
[0153] The present invention uses C / ZnO / chitosan as a drug carrier and small molecule 5-FU as a drug model to prepare a drug sustained-release system. The optimal conditions for drug encapsulation efficiency and drug loading were explored and the drug sustained-release performance of C / ZnO / chitosan was tested. The construction of the drug loading system and the controlled-release performance study showed that the effects of the drug / carrier mass ratio and stirring time on the loading performance of the C / ZnO / chitosan composite material were systematically investigated through a single-variable optimization experiment. When the mass ratio was 1:4 and the stirring time was 48 hours, the system reached the optimal loading parameters, and the encapsulation efficiency and drug loading were increased to 18.5% and 42.5%, respectively. The introduction of chitosan can provide more hydroxyl groups as cross-linking points, providing more sites for drug loading and increasing the drug loading amount. In vitro release kinetics showed that the C / ZnO / chitosan composite drug loading system has significant controlled-release performance for 5-FU. Specifically, compared to the uncompounded C / ZnO system (sustained-release time 24 hours, cumulative release rate 40.0%), the C / ZnO / chitosan system exhibited a prolonged sustained-release time of 39 hours and a cumulative release rate of 63.1%. This phenomenon can be attributed to the dense network structure formed by chitosan at physiological pH, which increases the specific surface area of the material and slows the drug diffusion rate. The study confirmed that the introduction of chitosan synergistically optimized the controlled-release performance of the drug. Comprehensive evaluation of the biocompatibility and antibacterial properties of the material showed that the hemolysis rate of the C / ZnO / chitosan composite met the requirements for biomedical materials and exhibited good biocompatibility. Antibacterial experiments demonstrated that the drug-loaded composite (C / ZnO / chitosan) exhibited excellent antibacterial activity against both Staphylococcus aureus and Escherichia coli, with superior antibacterial activity compared to the C / ZnO base material, as demonstrated by reductions in MIC / MBC values of approximately 17.0% (S. aureus) and 20.0% (E. coli), respectively.
[0154] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a C / ZnO / chitosan composite material, characterized in that: The following steps are involved: Step 1, uniformly dispersing zinc salt and carbon source in an organic solvent to carry out a solvothermal reaction to obtain C / ZnO; Step 2: Dispersing the C / ZnO and chitosan in solvent A, and reacting under alkaline conditions to obtain a C / ZnO / chitosan composite material.
2. The preparation method according to claim 1, characterized in that In step 1, the zinc source is zinc acetate; the carbon source is glucose; and the ratio of the zinc source to the carbon source is (2.00-2.40) mmol: (0.18-0.22) g.
3. The preparation method according to claim 1, characterized in that In step 1, the organic solvent is ethylene glycol.
4. The preparation method according to claim 1, characterized in that In step 1, the pH of the solvent thermal reaction is 10.1; the temperature of the solvent thermal reaction is 160° C., and the time is 24 h.
5. The preparation method according to claim 1, characterized in that In step 2, the mass ratio of the C / ZnO to the chitosan is (0.90-1.10):(0.90-1.10); the solvent A is an acetic acid aqueous solution with a mass concentration of 1%; the mass volume ratio of the C / ZnO to the solvent A is (0.90-1.10) g:(90-110) ml.
6. The preparation method according to claim 1, characterized in that In step 2, the pH of the reaction is 10; the temperature of the reaction is 60° C.; and the reaction time is 3 h.
7. The C / ZnO / chitosan composite material prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the C / ZnO / chitosan composite material according to claim 7 in the preparation of sustained-release drugs.
9. A sustained-release drug, characterized in that: The method is prepared by dissolving a C / ZnO / chitosan composite material and 5-fluorouracil in water and stirring the mixture under light-proof conditions.
10. The sustained-release drug according to claim 9, characterized in that: The mass ratio of the C / ZnO / chitosan composite material to the 5-fluorouracil is (0.25-2):1; and the stirring time is 12-48 hours.